UJI AKTIVITAS TABIR SURYA EKSTRAK ETANOL DAUN JERUK PURUT (Citrus hystrix DC) - qonitah, fadilah; Namirah, Siti; Ahwan (Sam Ratulangi University, 2024)
Sunscreen is a substance that can protect the skin from UV rays . One of the plants that can be used as a source of sunscreen is kaffir lime. Kaffir lime leaves contain secondary metabolites, namely flavonoids, phenols, and tannins that can potentially be used as sunscreens. The purpose of this study was to determine the sunscreen potential of the ethanol extract of kaffir lime leaves including the SPF value, the percent erythema transmission, and the percent transmission of pigmentation. Extraction of kaffir lime leaves using maceration method with 95% ethanol as solvent. Determination of sunscreen by UV-Vis spectrophotometry..The results show that at the highest concentration of 250 ppm ethanol extract of kaffir lime leaves with an SPF value of 17.29±0.45 (ultra protection). The percent value of erythema transmission at the highest concentration of 250 ppm ethanol extract of kaffir lime leaves with a %Te value (1,68±0.03)% (extra protection). The percent value of pigmentation transmission at the highest concentration of 250 ppm ethanol extract of kaffir lime leaves with a %Tp value of (5,54±0.02)% (sunblock).